Study of evolution and developmental mechanism of stamen in Salvia hypoleuca Benth. (Lamiaceae) and related taxa using Electron Microscopy and molecular phylogenetic tools - Maryam-Sadat Asadollahi; Taher Nejad-Sattari; Ali Sonboli; Iraj Mehregan (تاکسونومی و بیوسیستماتیک, 2014)
The genus Salvia L. includes a group of plants having two stamens with a special morphology. Natural groups within this genus consist of species with special type of stamen morphology. In this paper, phylogenetic placement and developmental stages of stamen of S. hypoleuca Benth. were studied. Examination of this and related species showed that each flower had two stamens with posterior thecae not expressed and the distal posterior ends of the adjacent connectives were fused into a complex structure blocking access to nectar. All species with such type of stamens grouped into a monophyletic clade with robust support. Study of stamen development in S. hypoleuca showed that normal, anterior thecae were evolved before the other organs and that the stamen found its final matured form before flower opened. In an opened flower, stamen and reproductive organs could be found in their final maturestage. In addition, it seemed that stamen development in related species should be similar.